Evaluation and Design Accessibility of Mosque’s Facilities for People with Disabilities - Iksan Widiantoro Restu Aji; Bambang Suhardi; Irwan Iftadi (Journal of Islamic Architecture, 2022)
The condition of the grand mosques in the Boyolali, Surakarta, and Karanganyar areas currently does not consider facilities that can accommodate people with disabilities. This study aims to improve the accessibility of mosque facili-ties and provide proposals for designing facilities that are accessible for mosque worshipers, including those with disabilities. The object of this re-search consists of several great mosques located in Boyolali, Surakarta, and Karanganyar. The accessible congregation is used to conduct access audits using a questionnaire to assess the level of accessibility as well as to deter-mine the priority of the selected mosque, and then design the mosque facili-ties using AutoCAD software concerning the Regulation of the Minister of Public Works and Public Housing No. 14 of 2017. The results of the congregation show that 4 mosques are not accessible and 1 mosque is less accessible. Based on the analysis, it shows that the Madaniyah Great Mosque located in Karanganyar was chosen to be the object of the proposed improve-ment because it has the highest accessibility index value and the current condition of the mosque is the most likely to be repaired, so that mosque facilities are accessible for people with disabilities. The proposal to improve facilities at the Great Madaniyah mosque is to provide a unique parking lot with a size of 5 m x 2.3 m, provide an incline with a slope of 5° and have handrails on both sides, provide two types of ablution places, namely with a seat and no seat, provide toilets equipped with kick plates, automatic hinges, panic buttons, and handrails; provide lifts with handles on all sides and a lift size of 120 cm x 230 cm; provide signs or signs in unique parking lots; add signposts; provide a particular prayer area and a special lane located close to the entrance to the prayer area.